Aqueous Morinda citrifolia Leaves Extract Enhancing Glutathione Peroxidase Activity and α2-Macroglobulin Gene Expression on Macrobrachium rosenbergii - Atika Marisa Halim; Arief Prajitno (Research Journal of Life Science, 2017)
Morinda citrifolia, known commercially as noni is often used for enhancing immunity, these plant-rich phenolic compound with antioxidant properties. In the present study, Macrobrachium rosenbergii were fed diets containing aqueous M. citrifolia leaves extract (AMLE) at 0.6, 4 and 6 g kg-1. Glutathione peroxidase (GPx) and α2-macroglubulin (α2-M)  activity were conducted to measure an immune parameter, which was evaluated before and after 7, 21, 35, 49 and 63 days of feeding trial. The results showed that after 63 days of feeding treatment, significantly increased in GPx activity. Moreover, the gene expressions of α2-macroglubulin was significantly upregulated. These results recommend that administration of AMLE can be used as an immunostimulant and regulated immune response and immune gene expression in M. rosenbergii.